Ties on the holy oils on the altars of the slave quarters: The ties of compadrio of liners and slaves in Arraial do Tejuco and Vila do Príncipe (1720-1740). - Ferraz Tavares Roque, Thassio (Temporalidades, 2021)
In this study we analyze the social pattern of the godparents of the baptized slaves of Arraial do Tejuco and Vila do Príncipe, in the period 1720-1740. Our methodological basis was the handling of the ecclesiastical sources of the Archdiocese of Diamantina-MG, and we centralized the research in the information contained in the baptism records. Crossing such data with the refinement of bibliographic references, we will try to make the characterizations of sponsorship practices more precise, and how they influenced the movement of captives in the face of social hierarchy. Our intention is to investigate which social actors the slaves sought more alliances with, and how they used the fissures of captivity, in the idealization of the conquest for freedom. We will obtain in this line of thought, hypotheses about the extent to which the experiment of the experience of the freedmen influenced the relations inside and outside the slave quarters. With this, we hope to show interpretative views that complement the understanding of the social relations of the colonial slavery period, using a spatial framework that is still little explored in the historiography on the subject.